Human interleukin 7: molecular cloning and growth factor activity on human and murine B-lineage cells. - Goodwin, R G (1989)
A cDNA encoding biologically active human interleukin 7 was isolated by hybridization with the homologous murine clone. Nucleotide sequence analysis indicated that this cDNA was capable of encoding a protein of 177 amino acids with a signal sequence of 25 amino acids and a calculated mass of 17.4 kDa for the mature protein. Recombinant human interleukin 7 stimulated the proliferation of murine pre-B cells and was active on cells harvested from human bone marrow that are enriched for B-lineage progenitor cells. Analysis of RNA by blot hybridization demonstrated the presence of two size classes of interleukin 7 mRNA in human splenic and thymic tissue.